Factor structure of Maslach Burnout Inventory (MBI-GS) in nursing staff of public health institutions - Castillo, Ronald (2020)
Introduction: This study examines the dimensionality of the Maslach Burnout Inventory (MBI-GS). Method: The sample was composed of 204 professional nurses from Peruvian health public institutions. The structural evaluation was conducted with confirmatory factor analysis using a estimator appropriate for the ordinal nature of the scale items. The assessed structure comprised of three correlated dimensions of exhaustion, cynicism and professional efficacy. Results: An acceptable fit was reached after removing two items from cynicism and allowing correlated errors in professional efficacy, χ²(73) = 156.61, CFI = .97, TLI = .93, RMSEA = .075. The internal consistency coefficients were adequate for each of the dimensions (ω >.80). Conclusion: The MBI-GS is an instrument that presents evidence of internal structure and reliability in a sample of nursing staff.